Effect of paclobutrazol on in vitro shoot growth suppression of Titan Arum (Amorphophallus titanum Becc.) - Suci Pratiwi; Gustian Gustian; Ryan Budi Setiawan (JURNAL AGRONIDA, 2026)
Titan arum (Amorphophallus titanum (Becc.)) is an endemic flora of Sumatra whose population has declined, placing the species at risk of extinction. Conservation efforts through in vitro culture are needed to support its preservation. In medium-term in vitro conservation, plantlet growth must be suppressed to prolong subculture intervals, reduce contamination risks, and lower maintenance costs. This study aimed to determine the optimum concentration of paclobutrazol for suppressing the shoot growth of A. titanum under in vitro conditions. The research was conducted from October 2024 to May 2025 at the Tissue Culture Laboratory, Universitas Andalas. The experiment was arranged in a randomized complete block design with four concentrations of paclobutrazol: 0, 1, 2, and 3 mg L⁻¹. Each treatment was replicated three times, resulting in a total of 12 experimental units. Data were analyzed using analysis of variance (F-test) at the 5% significance level, followed by Duncan’s Multiple Range Test (DMRT) at the 5% level when significant differences were detected. The results showed that paclobutrazol at 3 mg L⁻¹ was the most effective treatment for suppressing shoot height increment of A. titanum, resulting in a growth increase of only 0,2 cm and 0.17 cm. These findings indicate that paclobutrazol has potential as a growth-retarding agent for the medium-term in vitro conservation of A. titanum.